2016
DOI: 10.1002/ijgo.12031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an intervention initiated by a national society to improve postabortion care in rural facilities in Burkina Faso

Abstract: SOGOB's intervention has improved the quality of PAC in rural health facilities in Burkina Faso.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Medical treatment with Misoprostol is increasingly being used to treat incomplete abortions and is a cheap and safe way to induce contractions of the uterus and an evacuation in a natural way [ 20 , 24 , 25 ]. However, the QECH was the only hospital that used medical treatment, in just 3.2% (95 CI, 2.6–4.5) of the cases in 2015; medical treatment was mostly used to prepare patients for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Medical treatment with Misoprostol is increasingly being used to treat incomplete abortions and is a cheap and safe way to induce contractions of the uterus and an evacuation in a natural way [ 20 , 24 , 25 ]. However, the QECH was the only hospital that used medical treatment, in just 3.2% (95 CI, 2.6–4.5) of the cases in 2015; medical treatment was mostly used to prepare patients for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective, safe, acceptable and affordable method of miscarriage management; however, arrangements for appropriate clinical follow-up are necessary as there is a risk of incomplete expulsion of pregnancy tissue with this method. 74,75 Manual vacuum aspiration (MVA) is effective and safe for early pregnancies and is recommended by the World Health Organization to replace dilatation and curettage where these are still practiced. 76 However, a strategic assessment of unsafe abortion in Malawi found MVA is used infrequently, with dilatation and curettage being used in preference.…”
Section: Global Perspectivesmentioning
confidence: 99%
“…Nine decentralization studies (33%) showed improvement in one or more outcome measures including mortality, complication rate, or patient satisfaction. 26,32,33,35,37,40,48,50,51 All studies showing improved outcomes included workforce training and investment in infrastructure, equipment, or supplies as major components of their interventions. Five out of these nine studies (55.5%) included 4 or more intervention categories.…”
Section: Resultsmentioning
confidence: 99%